Performance and hormonal profile in broiler chickens fed with different energy levels during post restriction period - Giachetto, Poliana Fernanda; Guerreiro, Erika Nomura; Ferro, Jesus Aparecido; Ferro, Maria Inês Tiraboschi; Furlan, Renato Luis; Macari, Marcos (Pesquisa Agropecuaria Brasileira, 2003)
The aim of this work was to investigate the influence of diet energy level on performance and hormonal profiles of broilers during post restriction period. It was a split-plot experiment, and the main treatments were in a 2x2 factorial scheme. Birds were fed restricted to 30% of the ad libitum intake, from 7 to 14 days of age. After the restriction period, birds were fed ad libitum with diets containing low (2,900 kcal ME/kg) or high (3,200 kcal ME/kg) energy until 49 days of age. Broilers fed with high energy ration showed lower feed intake and better feed conversion and decreased carcass protein; however, abdominal fat pad, and total carcass fat were not affected by ration energy levels or feeding program. Neither diet energy level nor feed restriction program changed body weight at 49 days. The profile of insulin-like growth factor-1 (IGF-1) was reduced during the feed restriction period, but increased at refeeding period. Feeding program and ration energy level did not affect T3, T4 and growth hormone serum concentrations. Feed restriction at 30% of ad libitum intake is not enough to promote changes on carcass quality, related to fat deposition, and on metabolic hormone levels, except IGF-1 seric level that has rapid increase after feed restriction.
Keywords: carcass composition; weight gain; hormones; feeding level